The transition from oxygen chemisorption to oxidation of ultra-thin Ni layers on Cu(111) - Domnick, Ralph; Held, Georg; Witte, Patrick; Steinrück, Hans-Peter (Journal of Chemical Physics, 2001)
The oxygen chemisorption and oxidation of Ni monolayers on Cu(111) were studied by high resolution XPS. As a result, new insight in the electronic state of the top-most surface atoms during adsorption and reaction of molecules which cannot be retrieved from single crystal surfaces because of the dominating bulk signal was obtained.